The Missing Alternative Objection to Criminal Law Abolitionism - Zisman, Valerij (Diametros, 2023)
Criminal law abolitionists claim that legal punishment cannot be morally justified and that we should therefore abolish criminal law. While this is still a minority position in the current debate, the number of proponents has been increasing, and even opponents have developed a certain degree of sympathy for such claims in recent years. Yet one of the reasons many remain hesitant regarding the abolition of criminal law appears to be the lack of a thought-through alternative, in addition to abolitionists disagreeing considerably amongst themselves on what an alternative should look like. I will call this the missing alternative objection. To address this central concern, I will argue in this paper that the most prominent versions of abolitionism actually converge on the same alternative core to criminal law — even though they are driven by vastly different motivations. This core that current abolitionist theories converge on is two-fold: first, the claim that the state should compel offenders to provide restitution for the victim; second, the claim that restorative processes should be used wherever possible when addressing criminal wrongdoing. This common core is enough to reject the missing alternative objection.